Using Emancipation Checklists with Youths Aging Out of Foster Care: An Example from Prince George's County. (21st July 2021) - Shdaimah, Corey; Summers, Alicia; Park, Eunsong
Abstract: This study examined implementation of a 12‐item questionnaire, the Emancipation Checklist, designed to help child welfare judicial decision‐makers (JD) identify and monitor older youth achievement of milestones toward adulthood. Drawing on case file reviews, focus groups with professional stakeholders and young adults, and court observations, we found that stakeholders, including youths in foster care, viewed the EC as helpful in catalyzing conversation and follow up. Inconsistent use and documentation and ambiguity of some questions impeded its value. We provide recommendations for clear and consistent use, follow up, and further research to examine the impact of the EC on readiness for adulthood.